Low-voltage low-power FGMOS based VDIBA and its application as universal filter. Issue 2 (February 2015) - Gupta, Maneesha; Srivastava, Richa; Singh, Urvashi
Abstract This paper presents Floating gate MOS (FGMOS) based low-voltage low-power variant of recently proposed active element namely Voltage Differencing Inverting Buffered Amplifier (VDIBA). The proposed configuration operates at lower supply voltage ±0.75 V with the total quiescent power consumption of 1.5 mW at the biasing current of 100 µA. Further the operating frequency of the proposed VDIBA is improved by using the resistive compensation method of bandwidth extension in Operational Transconductance Amplifier (OTA) stage of the block. By using resistive compensation method of bandwidth extension, the bandwidth of OTA stage increases from 92.47 MHz to 220.67 MHz. As an application, proposed FGMOS based VDIBA has been used to realize a novel resistorless voltage mode (VM) universal filter. The proposed universal filter configuration is capable of realizing all the standard filter functions in both inverting and non-inverting forms simultaneously without any matching constraint. Other important features include independently tunable filter parameters, cascadibility and low sensitivity figure. The proposed filter is tunable over the frequency range of 4.1 MHz to 12.9 MHz and is capable of compensating for process, voltage and temperature (PVT) variation. The simulations are performed using SPICE and TSMC 0.18 µm CMOS technology parameters with±0.75 V supply voltage to validate the effectiveness of the proposed circuit.